2020
DOI: 10.1097/meg.0000000000001761
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength and physical performance, rather than muscle mass, correlate with mortality in end-stage liver disease

Abstract: Objectives Sarcopenia is characterized by the loss of skeletal muscle mass, strength and performance. The study aimed to provide cut off values of various Sarcopenia parameters [computerized tomography skeletal muscle index (SMI), handgrip strength (HGS), gait velocity and chair stand] to predict mortality in end-stage liver disease (ESLD). Methods The inclusion criteria were age 18–75 years, model for end-stage liver disease > 15. All patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The chair stand test in patients with CLD has been used as a parameter for frailty rather than sarcopenia [109][110][111]. The chair stand test was found to be an independent factor predictive of poor quality of life and waitlist mortality in patients with end-stage liver disease [110,112,113]. However, research on the usefulness of and appropriate cutoff values for the chair stand test in patients with CLD is still lacking.…”
Section: Chair Stand Testmentioning
confidence: 99%
“…The chair stand test in patients with CLD has been used as a parameter for frailty rather than sarcopenia [109][110][111]. The chair stand test was found to be an independent factor predictive of poor quality of life and waitlist mortality in patients with end-stage liver disease [110,112,113]. However, research on the usefulness of and appropriate cutoff values for the chair stand test in patients with CLD is still lacking.…”
Section: Chair Stand Testmentioning
confidence: 99%
“…Our results suggest that a combination of low HGS and low SMI is a better predictor of mortality in patients with cirrhosis compared with low SMI or low HGS alone. 11 Other studies from India have also shown that HSG correlates with mortality in patients with cirrhosis, 12 further validating the incorporation of low HGS in the diagnostic definition.…”
Section: Diagnostic Criteriamentioning
confidence: 83%
“…These include gait speed, chair stand, timed up and go test, short physical performance battery, and 400‐m walk test. The inability to perform these tests suggests severe sarcopenia, which correlates with poor outcomes in cirrhosis 12 . The INASL recommends a 4‐m usual walking gait speed of ≤0.8 m/s as an indicator of reduced physical performance.…”
Section: Estimation Of Physical Performancementioning
confidence: 99%
“…<0.001). Utilizing the recently derived Indian cutoffs for poor prognosis in cirrhotics7 , HGS≤ 25.3 kg force was noted in 53 (65%) patients and suboptimal chair-stand (≥ 20.9 seconds) was noted in 44 (54%)…”
mentioning
confidence: 99%